Neotame: High Intensity Low Caloric Sweetener - Satyavathi, K.; Bhoja Raju, P.; Bupesh, K.V.; Naga Ravi Kiran, T. (Asian Journal of Chemistry, 2010)
Neotame is an artificial sugar substitute which is N-alkyl derivative of aspartame. It is non caloric and 7000-13,000 times sweeter than sucrose, 30-60 times sweeter than aspartame respectively. It has excellent shelf life in dry conditions. Neotame is more stable in aqueous form at neutral pH. It is heat stable and consequently used in cooking and baking. Unlike aspartame it is safe for people with phenylketonurea. It is compatible with wide range of food ingredients, so blended with other caloric sweeteners to enhance taste and flavour. It doesn't show any significant toxicity and is non-carcinogenic. Neotame is a highly potent sweetener that can be used to modify and enhance flavour of foods and beverages.